Genetic diversity and phylogenetic status of Punganur cattle based on mtDNA analysis - CHANDAKA, DEEPTHI; METTA, MURALIDHAR; REGULA, VINOO; KAZA, SUDHAKAR; KROVVIDI, SUDHAKAR (The Indian Journal of Animal Sciences, 2024)
The Punganur is distinctive Indian cattle breed that has witnessed a decline in purity due to uncontrolled cross- breeding practices. This study aims to assess the genetic diversity and phylogenetic status of Punganur cattle by analyzing the mtDNA D-loop region. mtDNA D-loop sequences generated from 47 individuals belonging to Punganur breed, cattle similar to Punganur breed, other dwarf cattle breeds and 165 additional sequences representing Bos taurus and Bos indicus from the database were used for comparative analysis. 119 polymorphic sites and 130 haplotypes were observed, with an overall haplotype and nucleotide diversity of 0.988 and 0.028, respectively. Phylogenetic analysis indicated a lack of clear demarcation between Punganur and Punganur Type animals. A Holstein animal clustered with a Punganur Type (PP12) animal, suggesting a connection to the cross- breeding program in the country. Based on the mtDNA D-loop region, Punganur and Punganur Type animals could not be differentiated, emphasizing the need for additional molecular tools and a larger sample size to address this question adequately. This study highlights the urgency of preserving the genetic integrity of Punganur cattle and calls for further comprehensive analyses to elucidate their true phylogenetic relationships.